SIZE DISTRIBUTION AND SORTING DEGREE OF THE RECENT SEDIMENTS OF AL-KHAZER RIVER/ NORTHERN IRAQ - Khalid F. Hassan (Mesopotamia Journal of Agriculture)
Mechanical and statistical analysis were conducted to determine the grain size distribution and sorting degree of the recent sediments of Al-Khazer river at northern of Iraq in order to clarify the sedimentation processes along this river. The study was carried out after the annual flood time of the river. Sediment size distribution was determined mechanically for major grain size fractions [gravel (-2 phi to 0 phi), sand (0 phi to +4 phi), silt (+5 phi to +7 phi)] and clay (+8 phi)] using sieve and pipette technique. Numerical treatment of grain size curves has been done on the basis of some quintiles read from the empirical cumulative distribution function (CDF) curve: phi median size, sorting, skewness and kurtosis. The results showed that the sediments of this river were relatively coarse grained textured (Ø50=0.35 to 1.2 phi), very poorly sorted, showing strongly coarse skewed towards fine particles and are platy to leptokurtic. The increase in phi toward outlet plain is equivalent to decrease in grain diameter and is indicative of a lower energy and higher depositional environment. For this reason, there are some relatively lower phi values in the inlet plain in comparison with the phi values of outlet plain. On the basis of this assumption, the change in sediment-size distribution along the river is a non-linear fashion and can be inferred from that to which the present deposition takes place by bed or graded suspended load.